2022
DOI: 10.3390/ijfs10040101
|View full text |Cite
|
Sign up to set email alerts
|

Financial Uncertainty from a Dual Shock at Global Level–Insights from Kuwait

Abstract: Global stock markets experienced a dual shock in 2020 due to the impact of the global health crisis, parallel to a simultaneous shock derived from the Saudi Arabia and Russia oil price war. The dual shock fueled oil market volatility with lasting effects as the global economy is immersed in an energy crisis combined with high inflationary pressures exacerbated by heightened energy costs. This research paper implemented GARCH and FIGARCH models on daily returns from 31 December 2015, to 9 December 2021, to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Volatility persistence is a crucial phenomenon to analyze in stock markets as it provides insights into the dynamics of market uncertainty and risk (Alotaibi, & Morales, 2022). Numerous empirical studies have consistently found evidence of volatility persistence in stock markets (Baek, Mohanty & Glambosky, 2020;Magner, Lavin,Valle & Hardy, 2021;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Volatility persistence is a crucial phenomenon to analyze in stock markets as it provides insights into the dynamics of market uncertainty and risk (Alotaibi, & Morales, 2022). Numerous empirical studies have consistently found evidence of volatility persistence in stock markets (Baek, Mohanty & Glambosky, 2020;Magner, Lavin,Valle & Hardy, 2021;.…”
Section: Literature Reviewmentioning
confidence: 99%